Social functions of mentors for graduates of orphanages (on the example of Novosibirsk) - E. A. Popov (RUDN journal of Sociology, 2023)
The study of the phenomenon of mentoring is determined by challenges in the social existence of individuals and groups that find themselves in a difficult life situation. The article focuses on the graduates of organizations for orphans and children left without parental care, who face adaptive, social and social-cultural difficulties after leaving the orphanage, and in this situation the role of mentors is crucial. Based on the semi-structured interviews with mentors (N = 17) and graduates (N = 15) of orphanages in Novosibirsk, the author identifies social functions of mentors and the graduates’ attitude to them. Novosibirsk was chosen as the first city in Russia, in which mentoring system for graduates of orphanages was tested. The article focuses on the social functions of mentors based on the idea that the social function is an effective means for achieving goals that are significant for society or its groups. The following social functions of mentors were identified: socializing, social-communicative and social-cultural. These functions allow to define mentoring not only as a pedagogical phenomenon, but also as a social practice that determines the interaction of representatives of different social groups/communities. Such interaction is purposeful, reflects the completeness of the subjects’ life worlds and their value orientations, forms meaningful attitudes and improves the quality of life in general. The study showed that the interaction between mentors and graduates is positive and contributes to the improvement of the graduates’ social life. The author identifies the key markers of the mentors’ attitude to the social practices of the orphanage, their estimates of its role in the formation of personality and value orientations. The approach presented in the article allows to consider mentoring as an important factor of socialization.